Potensi Substitusi Tepung Ulat Hongkong (Tenebrio molitor) Dalam Pakan Buatan Terhadap Pertumbuhan Benih Ikan Platy (Xiphoporus maculatus) - Dwijowati Asih Saputri; Tinto Dwi Nata (Institut Agama Islam Negeri Kerinci, 2024)
The Hong Kong caterpillar, which comes from the Tenebrio molitor (TM) insect, contains high levels of protein and fat so it can be used as a substitute for fish meal in fish farming feed, including for platy fish. The aim of this research was to evaluate the effect of substituting Tenebrio molitor larva flour on the growth and survival of platy fish fry, as well as on the pH and water temperature over a period of 28 days. The study was conducted using a Completely Randomized Design with five treatments and three replications. The treatments included control, addition of Hong Kong caterpillar flour at 25% (P1), 50% (P2), 75% (P3) and 100% (P4). Parameters measured included weight and length gain of the fish, survival rate, pH, and water temperature. The research data was analyzed using analysis of variance with SPSS software followed by Least Significant Difference test (LSD). The results showed that substituting feed with TM larva flour could increase both weight gain and length in platy fish compared to the control without reducing survival rates. The best substitution for the growth of platy fish fry was found to be at 100% substitution level (P4). Substitution using TM larva flour also did not cause changes in water temperature or pH levels allowing for healthy growth of platy fry.From these findings it can be concluded that TM larva flour can be used as a substitute for commercial feed as a protein source in feeding platy fry.